Continuity or Change? Political Economics of Post-Crisis Argentina and the Néstor Kirchner Administration, 2003-2007 - Wylde, Christopher (2012)
This article focuses on the government policies implemented by Néstor Kirchner as a response to the 2001-2002 Argentine crisis and reviews the country’s subsequent development. Focusing on the different areas of political-economic analysis, it will demonstrate that the government (2003-2007) launched a number of key policy changes that followed Carlos Menem’s neoliberal regime. These changes provided a new path of development for Argentina and were the product of a deliberate construction by the Kirchner government, which operated under favorable international circumstances.